Pelatihan computational thinking guru MI se-Kecamatan Pabelan, Kabupaten Semarang - Kusumawati, Erna Risfaula; Achmad, Syaefudin (Nur Science Institute, 2022)
Learning in society 5.0 and the covid-19 pandemic requires several skills to be mastered, both by students and teachers. These skills are creativity, critical thinking, communication, collaboration, compassion, and computational thinking (6C). This paper describes the training carried out on teachers to improve computational thinking skills. A teacher must master computational thinking to prepare the next generation of potential, superior, and ready to face the era of society 5.0. The training target is MI teachers in Pabelan District, totaling 26 teachers. The training was divided into several stages, including a pretest, material presentation, practice working on logarithmic problems, creating a Bebras account, tutorial on making games using scratch software, and posttest. At the end of the activity, participants are asked to fill out a presence link as a condition to get a certificate. The training results showed that most of the participants could understand and implement computational thinking. It can be seen from the results of the posttest given. Participants were very enthusiastic and active in participating in the training. They were also happy because follow-up activities after the training were completed.